2022
DOI: 10.1136/bmjgast-2022-001001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety and tolerability of the CREB-binding protein/β-catenin inhibitor OP-724 in patients with advanced primary biliary cholangitis: an investigator-initiated, open-label, non-randomised, two-centre, phase 1 study

Abstract: ObjectiveThis study aimed to evaluate the safety and tolerability of OP-724, a CREB-binding protein/β-catenin inhibitor, in patients with advanced primary biliary cholangitis (PBC).DesignAn open-label, non-randomised, phase 1 trial was conducted at two hospitals in Japan. Patients with advanced PBC classified as stage III or higher according to the Scheuer classification by liver biopsy between 4 September 2019 and 21 September 2021 were enrolled. Seven patients received intravenous OP-724 infusions at escalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Overall, the only AE reported was diarrhoea (1/5 patients, 20.0%). Diarrhoea is a side effect that also appeared as a gastrointestinal symptom in the previously conducted PRI-724-2101 study—a study conducted in patients with liver cirrhosis caused by HCV or HBV 12. This AE was manageable by monitoring the progress and administering appropriate symptomatic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the only AE reported was diarrhoea (1/5 patients, 20.0%). Diarrhoea is a side effect that also appeared as a gastrointestinal symptom in the previously conducted PRI-724-2101 study—a study conducted in patients with liver cirrhosis caused by HCV or HBV 12. This AE was manageable by monitoring the progress and administering appropriate symptomatic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the plasma concentration of the investigational drug and determine changes in the PK parameters, the PK parameters obtained in this clinical trial were compared with those of a previous study, PRI-724-2101, and population PK parameters 12. The relationship between safety and PK was also assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An open-label phase 1 trial showed in patients with advanced PBC, intravenous OP-724 infusion was well tolerated. Although it did not significantly improve liver function, its anti-fibrotic effects were indicated by decreased in collagen in livers of PBC patients with advanced fibrosis ( 112 ).…”
Section: Novel Advances Targeting Immune Factorsmentioning
confidence: 99%